The Mutographs biorepository: A unique genomic resource to study cancer around the world - Sandra Pérdomo; Behnoush Abedi‐Ardekani; Ana Carolina de Carvalho; Aida Ferreiro-Iglesias; Valérie Gaborieau; Thomas Cattiaux; Hélène Renard; Priscilia Chopard; Christine Carreira; Andreea Spanu; Arash Nikmanesh; Ricardo Cortez Cardoso Penha; et al. (2024)
Large-scale biorepositories and databases are essential to generate equitable, effective, and sustainable advances in cancer prevention, early detection, cancer therapy, cancer care, and surveillance. The Mutographs project has created a large genomic dataset and biorepository of over 7,800 cancer cases from 30 countries across five continents with extensive demographic, lifestyle, environmental, and clinical information. Whole-genome sequencing is being finalized for over 4,000 cases, with the primary goal of understanding the causes of cancer at eight anatomic sites. Genomic, exposure, and clinical data will be publicly available through the International Cancer Genome Consortium Accelerating Research in Genomic Oncology platform. The Mutographs sample and metadata biorepository constitutes a legacy resource for new projects and collaborations aiming to increase our current research efforts in cancer genomic epidemiology globally.